Alien vs. Predator : Requiem - Aylesworth, Reiko, 1972-; Lewis, Johnny; Ortiz, John.; Pasquale, Steven (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2008)
A small Colorado town becomes the battleground between two of the deadliest extra-terrestrial lifeforms - the Alien and the Predator. When a Predator scout ship crash-lands in the hills outside the town, Alien facehuggers are released in the crash. Also released is a hybrid Alien/Predator. A man and his son hunting in the forest near the crash site soon become the first victims of the facehuggers. A Predator receives data about the crash on his home planet and he comes to Earth. One at a time, the inhabitants of the town become targets of the Aliens and the Predator. The National Guard is called in, but they are unable to stop the deadly creatures. A plan is set in motion to destroy the town with a nuclear device.
Based on the 'Alien' characters created by Dan O'Bannon and Ronald Shusett ; based on the 'Predator' characters created by Jim Thomas and John Thomas.
Originally released as a motion picture in 2007.
Special features: Full-length audio commentary by directors Colin and Greg Strause and producer John Davis; full-length audio commentary by creature effects designers/creators Alec Gillis and Tom Woodruff, Jr; added footage marker; theatrical trailers.
Title from container.
Director of photography, Daniel C. Pearl ; editor, Dan Zimmerman ; music, Brian Tyler ; costume designer, Angus Strathie ; production designer, Andrew Neskoromny ; creature effects designers/creators, Alec Gillis, Tom Woodruff Jr.
Steven Pasquale, Reiko Aylesworth, John Ortiz, Johnny Lewis, Ariel Gade.
Keywords: Extraterrestrial beings -- Colorado -- Drama; Feature films; Human-alien encounters -- Colorado -- Drama; Predation (Biology) -- Colorado -- Drama; Video recordings for the hearing impaired